NANO g∗α- NORMAL SPACES IN NANO TOPOLOGICAL SPACES - ADINATHA C. UPADHYA (Kongunadu Research Journal, 2025)
The aim of this paper, we introduce a new class of nano normal spaces in a nano topological space. We obtain the relationships of such normal spaces and present some properties and establish various preservation theorems.